Analytical study of upper gastrointestinal endoscopy findings in patients with dysphagia - النابلسي, إبراهيم; حسان زيزفون; رنا عيسى (Latakia University Journal -Medical Sciences Series, 2022)
Background: Dysphagia is the medical term for symptoms of difficulty in swallowing. Dysphagia can occur in all age groups, and its prevalence increases with aging. Diagnosis of dysphagia is important due to associated morbidity and mortality, so it warrants early evaluation. Upper gastrointestinal Endoscopy is one of the first investigational procedures in the assessment of dysphagia. Aim of the study: to determine the frequency of common endoscopic findings in patients presenting with dysphagia, and the utility of endoscopic biopsies in patients with normal upper endoscopy. Methods: This is a prospective, descriptive study conducted in the gastroenterology department in Tishreen University Hospital in Syria between 2020 and 2021. Results: A total of 57 patients; 34 females (59.6%), and 23 males (40.4%) presenting with dysphagia were studied, the mean age was 56.5 ± 18.6 years. Normal endoscopy was the most common findings noted in 24 (40.1%) patients, followed by esophageal cancer noted in 7 patients (12.3%), benign strictures in 6 patients (10.6%). Findings consistent with achalasia, gastro-esophageal reflux disease and external compression were each found in 5 patients (8.8%), while candidal esophagitis and esophageal webs/rings were found in 2 patients each (3.5%). Finally, eosinophilic esophagitis was found in one patient (1.8%). We observed the absence of histopathological changes in two thirds of the normal upper gastrointestinal endoscopy patients, and most of these patients were males, while reflux oesophagitis was diagnosed in the remaining third and most of them were females. Conclusions: Esophageal cancer is the most common abnormal finding in upper endoscopy for patients with dysphagia, and it is more common in males, followed by benign strictures, they are more common in females. One third of the normal upper GI endoscopy patients had histopathological findings consistent with reflux oesophagitis